Loving people who are hard to love : transforming your world by learning to love unconditionally - Meyer, Joyce, 1943- (FaithWords, 2022)
"How do you love the people in your life who are hard to love? We're never going to be able to prevent people from saying or doing things that hurt our feelings. We will always have opportunities to get offended. But if we do things God's way, we can choose to save ourselves a lot of misery and hardship. This doesn't mean we allow people to abuse us. No, there is a time for confronting people and dealing with situations. However, the Bible commands us to love our enemies and forgive those who have wronged us, even when it feels impossible. Everything the Lord asks us to do in the Bible is ultimately for our good. In fact, when we choose to love our enemies and forgive those who have hurt us, we are actually helping ourselves more than anyone else. Because whatever the Lord commands us to do, He is going to give us the power of the Holy Spirit to accomplish it-and that includes loving and being good to difficult people! God's love flowing through us is strong enough to melt even the hardest hearts, so use kindness as a weapon to overcome the meanness in people"--